(untitled) (Nexo Revista Científica, 2020)
The palm (Phoenix Dactylifera) is one of important trees, and is economically important in south of Iran. Date palm is propagated by the offshoots, number of which is limited. Therefore, adult Date palms produce shoot tips and axillary shoot meristems through the use of a tissue culture. This study was conducted to perform in -vitro tissue culture direct shoot regeneration and determine the best combination of plant regulators and other conditions. To achieve organogenesis and multiplication directly from shoot tips and axillary shoot meristems of Date palm (Phoenix Dactylifera L. Var Pyarum) was used without callus formation. Direct regeneration of vegetative buds minimizes the risk of somaclonal variation among plant regenerates. Results revealed that MS medium supplemented with 4mg/l of kinetin and 3 mg/l of IAA or 2mg/l of BA and 4 mg/l of NAA was the best formation from shoot tip after 16-20 weeks. Subculture per month was evaluated at following conditions: temperature for growth of 27±1°C during the lighted period and 22±1°C during the dark period.